2017
DOI: 10.1002/app.45201
|View full text |Cite
|
Sign up to set email alerts
|

Effects of compatibility on foaming behavior of polypropylene/polyolefin elastomer blends prepared using a chemical blowing agent

Abstract: Polypropylene (PP) exhibits poor foaming property because of its low melt strength arising from its linear chains and relatively narrow molecular weight distribution. To fabricate a PP foam without crosslinking, PP should be blended with polyolefin elastomers (POEs) using chemical blowing agents. In this study, the effects of POE types and contents in a PP matrix were studied by analyzing the melt flow index, morphology, and thermal and dynamic viscoelastic properties. Furthermore, the POE type/content and foa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In comparison, with longer annealing, the phase domain size increased, which led to the weakened heterogeneous nucleation and the relatively strengthened homogeneous nucleation. The previous studies also reported the decreased cell density due to the coalescence of phase domains.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…In comparison, with longer annealing, the phase domain size increased, which led to the weakened heterogeneous nucleation and the relatively strengthened homogeneous nucleation. The previous studies also reported the decreased cell density due to the coalescence of phase domains.…”
Section: Resultsmentioning
confidence: 76%
“…In addition, the cell structure of the PS40/PMMA60 blend foam is significantly dependent on its phase morphology before foaming. With a short period of annealing, the phase domain size was relatively small with a large amount of interface areas, which was favorable for the heterogeneous cell nucleation and thus endorsed uniform cell structure . In comparison, with longer annealing, the phase domain size increased, which led to the weakened heterogeneous nucleation and the relatively strengthened homogeneous nucleation.…”
Section: Resultsmentioning
confidence: 99%
“…All composites showed the characteristic peaks of the α-monoclinic phase planes (110), ( 040), ( 130), ( 041), ( 060), (220), and (202), and a small peak of the β-hexagonal phase (300). With the addition of CW in pure iPP, the β-hexagonal peaks appeared at 2θ = 15.9°, which is observed in all composites [21,27,30]. In all composites, a reduction in peak intensity and sharpness were evident because of a lessening in the amount of the polymer matrix, as evidenced in Fig.…”
Section: Fig 8 Xrd Pattern Of Pure Ipp and Compositesmentioning
confidence: 63%
“…Polyolefin Elastomer (POE) has excellent properties, such as superior elasticity, strong tensile strength, excellent thermal stability, aging resistance, weather resistance, resistance to ozone, resistant to chemical media, low density, easy processability, and low cost. Therefore it is widely used for impact modifier (Kim et al, 2017;Yang et al, 2020a;Yang et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%